Emotive Figures as "Shown" Emotion in Italian Post-Unification Conduct Books (1860-1900) - Paternoster, Annick (Informal Logic)

(untitled) (Informal Logic, 2019)
Within a digital corpus of 20 Italian post-unification conduct books (1860 to 1900), UAM CorpusTool is used to perform a manual annotation of 13 emotive rhetorical figures as indices of “shown” emotion (émotion montrée, Micheli 2014). The analysis consists in two text mining tasks: classification, which identifies emotive figures using the 13 categories, and clustering, which identifies groups, i.e. clusters where emotive figures co-occur. Emotive clusters mainly discuss diligence and parsimony—personal values linked to self-improvement for which reader agreement is not taken for granted. In this corpus they function as “moving” values, that is, values acting recurrently as contexts for “argued” emotion (émotion étayée, Micheli 2014).